Global Strategy in Safe Motherhood: A Prospective Cross-Sectional Study on Birth Preparedness and Complication Readiness at Malda Medical College and Hospital - Suresh Chandra Mondal, Soham Chowdhury, Arijita Paria, Sunali Sabat (South Eastern European Journal of Public Health, 2025)
This study evaluates the knowledge and practices of Birth Preparedness and Complication Readiness (BPCR) among 100 primi gravida mothers attending the antenatal clinic at Malda Medical College and Hospital. Using a structured questionnaire, demographic data, knowledge scores and practice levels were assessed. In the outcomes, it was determined that 57 per cent of students come from nuclear families, and 53 per cent of them live in rural areas. Of these respondents, 61% had moderate to good knowledge of BPCR, while 39% had poor knowledge of BPCR Hence there are knowledge deficits among the target population about warning signs, emergency preparedness, and delivery services. Practices related to BPCR were categorised as poor (25%), moderate (50%) and good (25%), with rural and less-educated participants scoring lower. A positive correlation between education level and knowledge scores underscores the importance of maternal education in enhancing BPCR outcomes. The study concludes with recommendations to improve maternal health through targeted education programs, better access to antenatal services and community-level interventions.